Calvin and Augustine - Warfield, Benjamin Breckinridge (Presbyterian and Reformed Publ. Co., 1956)
pt. 1. John Calvin: John Calvin: the man and his work.--Calvin's doctrine of the knowledge of God.--Calvin's doctrine of God.--Calvin's doctrine of the trinity.--Calvinism.--Pt. 2. Augustine: Augustine.--Augustine and his "Confessions".--Augustine's doctrine of knowledge and authority.--Appendix: Calvin as a theologian